2014
DOI: 10.1089/pho.2013.3617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre- or Post-Exercise Low-Level Laser Therapy (830 nm) on Skeletal Muscle Fatigue and Biochemical Markers of Recovery in Humans: Double-Blind Placebo-Controlled Trial

Abstract: Laser application either before or after fatigue reduced the post-fatigue concentrations of serum lactate and CK. The results were more pronounced in the post-fatigue laser group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 28 publications
0
41
2
1
Order By: Relevance
“…It has been explained in the current study that both 10% EEC and LLLT have similar effects on LDH activity. Previous studies have reported a significant difference in LDH activity as compared to control, placebo, 35 and other interventions. 36 In accordance with this study, serum LDH activity remained elevated 48 hours after muscle damage.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been explained in the current study that both 10% EEC and LLLT have similar effects on LDH activity. Previous studies have reported a significant difference in LDH activity as compared to control, placebo, 35 and other interventions. 36 In accordance with this study, serum LDH activity remained elevated 48 hours after muscle damage.…”
Section: Discussionmentioning
confidence: 89%
“…Lavender and Nosaka 4 reported no significant difference in changes in CK activity when compared to control. Another study showed that CK activity is less in 10% EEC group as compared to control, 11 and Dos Reis et al 35 reported that the application of laser before and after exercise reduced the level of CK. Baroni et al 12 found that LLLT provided protection and reduced the level of CK when compared to placebo.…”
Section: Discussionmentioning
confidence: 94%
“…These energy doses are similar to doses emitted by diode lasers in a previous study [24], reinforcing the idea that light is light [37] and there is not a large difference between these light sources to prevent exerciseinduced muscle damage (CK) if the total dose applied per muscle group is adequate. However, it is important to remark that it is possible that the light dose used to prevent muscle damage with LEDT in a pre-conditioning regimen may not be the same dose necessary if the light therapy is applied after the exercise [38]. It is accepted that cells under biochemical or mechanical stress have better responses to light [39] than cells in homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The latter demonstrated a decrease in the skeletal muscle damage related to the exercise and a delay in muscle fatigue, enhancing skeletal muscle performance in both healthy volunteers and athletes. Moreover, dos Reis et al 15 demonstrated that LLLT either before or after fatigue protocol reduced the concentrations of serum lactate and CK in male soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent systematic reviews demonstrated that LLLT attenuates the muscle's inflammatory mediators and enhances activity of antioxidant enzymes when applied after or before exercise 11 - 13 . Thus, these physiological adaptations could improve muscular performance and decrease fatigue during physical exercise programs 7 , 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%